New records and interesting data for the Sardinian spider fauna (Arachnida: Araneae) - Caria, Michele; Pantini, Paolo; Alamanni, Federico; Ancona, Cesare; Cillo, Davide; Bazzato, Erika (Fragmenta entomologica, 2021)
We present new distributional data of 24 spider species in Sardinia, including 7 endemic and 1 poorly recorded species. Sixteen species from 7 families and six species from 2 families are recorded for the first time in Sardinia and Italy, respectively. Among these, the reported presence of Cepheia longiseta and five other species allows us to include the Synaphridae family and five genera (Anagraphis, Hahnia, Minyriolus, Thaumatoncus, Trabea) in the Sardinian spider checklist, and two genera (Anagraphis and Thaumatoncus) in the Italian spider checklist. Relevant faunistic and distribution notes of poorly collected species are also provided.